Analysis of User Satisfaction of Acces by KAI Application Using User Experience Questtionnaire (UEQ) Method - Lailatul Qomariyah; Prita Dellia; Vella Sifa Nurhidayati; Aristya Miftahun Nur Risky; Zidan Zam Zami (Jurnal Riset Informatika, 2025)
including in the transportation sector. Advances in information technology have encouraged companies to innovate in providing faster, more practical, and efficient services to meet user needs. One of them is PT Kereta Api Indonesia officially releasing the access by KAI application. However, in the access by KAI application there are indications of poor user experience which shows user dissatisfaction in using the access by KAI application. This study aims to determine the extent to which the Access by KAI application meets user expectations in terms of ease of use, effectiveness in helping users achieve their goals, and to determine the level of user experience felt during the use of the application. The method used in this study is the User Experience Questionnaire (UEQ) method to measure user experience with 6 assessment scales including attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. The results of the UEQ questionnaire showed that respondents had a positive impression of the Access by KAI application where the survey results showed a positive evaluation with a mean value> 0.8 and all aspects of the Access by KAI application were categorized in "Above Average" this means that in general it has quite good performance but still needs improvement.